CITRA PEREMPUAN DALAM NOVEL THE HOLY WOMAN: SATU KAJIAN FEMINIS (The Image of Woman in “The Holy Woman”: A Feminism Study) - Nur Sakinah, R. Myrna (Balai Bahasa Jawa Barat, 2014)
Penelitian ini memaparkan citra perempuan dalam novel The Holy Woman karya Qaisra Shahraz. Citra perempuan yang terungkap dalam novel The Holy Woman tidak lepas dari isu-isu seputar perempuan yang berada dalam kekuasaan patriarki, yaitu kekuasaan yang cenderung menempatkan perempuan sebagai korban. Teori yang digunakan adalah teori feminis yang diungkapkan oleh Mary Ann Ferguson yang melihat feminitas perempuan sebagai perempuan yang diidealkan (The Submissive Wife) dan perempuan sebagai objek seks (The Sex Object). Hasil yang ditemukan adalah citra The Submissive Wife atau perempuan yang diidealkan menunjukkan perempuan sebagai istri atau anak perempuan yang dapat memberikan kebahagiaan dan ketentraman untuk keluarganya, dan The Sex Object atau perempuan sebagai objek seks telah menunjukkan adanya politik dan kekuasaan patriarki.Abstract:This research is aimed at explaining how the image of woman in Qaisra Shahraz’s “The Holy Woman”. It dwells on women’ issues in a patriarchal power, that is, treating women as victims. The study applies Mary Ann Ferguson’s feminism theory. Her view considers that woman feminism is from (a) the submissive wife (idolized woman) and (b) the sex object (woman as sex object). The research concludes that (a) the submissive wife —either as wife or as daughter—can give happi- ness and peace for her family;(b) the sex object indicates that there has been an involvement both a political and a patriarchal power.